Teacher Challenges and Solutions in Teaching EFL Students - Putra, Ida Bagus Yoga Buana Surya (STKIP AGAMA HINDU SINGARAJA, 2021)
The present study was aimed at identifying the EFL teacher challenges in teaching English, EFL learners’ problems in the classroom from teacher’s perspective, and the EFL teacher’s solutions for the problems exist in the classroom activity at SMK Negeri 1 Gianyar. A qualitative method was used to identify an EFL teacher challenges and solutions in teaching English. An interview was done through Google Form and WhatsApp chat with the participant. The results revealed that there are two main challenges faced by the teacher and four main challenges faced by the students based on the teacher’s perspective. Additionally, the study also revealed the teacher’s solutions for the challenges appeared during the English teaching process. Further, it is suggested for the teacher to use jigsaw strategy in teaching that will make the students take an important part in teamwork instead of without doing nothing in a group activity.